Interactions Between Specific Immune Status of Pregnant Women and SARS-CoV-2 Infection - Chen, Ruirong; Zhang, Shaofen; Su, Sheng; Ye, Haiyan; Shu, Haihua (Frontiers in Cellular and Infection Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the pathogen responsible for the Corona Virus Disease 2019 (COVID-19) global pandemic. Because it is a new and highly contagious coronavirus, most people lack immunity to it, especially pregnant women. It is therefore important to understand the interaction between why pregnant women are susceptible to SARS-CoV-2 and the specific immune systems of pregnant women. Here, we provide an overview of the changes in the immune system during pregnancy, the activation and response of the immune system in pregnant women with COVID-19, adverse pregnancy outcomes in pregnant women with COVID-19, and treatment and prevention of COVID-19 in pregnant women.